INFLAMMATION, SLEEP DISTURBANCES AND THEIR RELATIONSHIP TO DEPRESSIVE SYMPTOMS DURING THE PERINATAL PERIOD - William, Simpson (My University, 2016)
Introducton: The pathophysiology of perinatal depression is not completely under- stood. Advances in our understanding of Major Depressive Disorder (MDD) suggests that inflammation and sleep disruptions are important pathophysiological factors. The unique biological interactions between immune functioning, sleep disruptions and the Hypothalamic Pituitary Adrenal (HPA) axis may make these factors especially impor- tant for the development of depression during the perinatal period. The goal of this thesis was to thoroughly examine both inflammation and sleep disruptions from late pregnancy through the early postpartum period and assess how they might be related the development of depressive symptoms. Results: Pregnancy IL-6 and IL-10 emerged as significant predictors of postpartum de- pressive symptoms. None of our other candidate inflammatory markers were associated with depressive symptoms during pregnancy, at 12 weeks postpartum or over time. Sig- nificant relationships were observed between mild depressive symptoms and disruptions in daily rhythms during pregnancy and at 3 months postpartum. We observed signif- icant trait level differences in objective measures of sleep in women at higher risk for PPD (i.e those with a history of recurrent MDEs). Significant differences in the rela- tionship between sleep and depressive symptoms across the perinatal period were also observed. For women with a history of recurrent MDEs, depressive symptoms during pregnancy appeared to be a trait rather than state phenomena. Our work is also the first to provided evidence linking objective (duration, efficiency and wake after sleep onset (WASO)) sleep parameters with small, but significant increases in IL-6 from late pregnancy to 12 weeks postpartum. Conclusion: In sum, our results fail to show a state association between biomarkers of inflammation and perinatal depressive symptoms. Our work indicates that diagnostic history modulates the relationship between sleep and perinatal depressive symptoms. This diagnostic history also modules the trajectory of these sleep parameters from late pregnancy to early postpartum. Finally, our results provide foundational evidence for an interaction between inflammation and sleep disturbances across the perinatal period.